Increasing latrine sales among poor households in rural Cambodia using targeted subsidies: a randomized control trial. (21st October 2022) - Nicoletti, Chris; Lestikow, Greg; Veasna, Toeur; May, Alicia; Macaranas, Reimar; Hudner, Daniel; Harper, James
Abstract: Because improved sanitation can improve public health but is lacking in many rural areas, many organizations use sanitation marketing to increase latrine coverage. In rural Cambodia, iDE has facilitated the sale of more than 395, 000 pour-flush latrines since 2011 but recognizes that market actors are not incentivized to sell to the poorest households. Using a randomized controlled trial, in which poor households in treatment villages were offered partial latrine subsidies, this study investigated how subsidies affected latrine sales and program cost-effectiveness. Results show latrine sales among poor households that were offered subsidies increased by 14–16% compared to those that were not offered subsidies. Also, no significant effect on latrine sales among non-poor households was found, although lower village-level latrine coverage can reduce latrine sales to non-poor households. Cost-effectiveness analysis shows the increase in sales and thus economies of scale from subsidies yield lower per-latrine program costs compared to non-subsidy costs (38 vs. 54). Well-targeted latrine subsidies can significantly increase latrine sales among poor households with minimal impact on latrine sales to non-poor households and favorable program cost reductions. However, subsidies must not be introduced into a market before baseline sanitation coverage is achieved to avoid market distortion effects. HIGHLIGHTS: Latrine sales among poor households that were offered subsidies increased by 14–16%. Subsidies for poor households can increase latrine sales without affecting sales to non-poor households. Increased latrine sales from subsidies can lower per-latrine program costs. Subsidies must not be introduced too early to avoid market distortion effects. Local market knowledge is required to accurately target latrine subsidies. Graphical Abstract